Airborne and Underwater Noise Produced by a Hovercraft in the North Caspian Region: Pressure and Particle Motion Measurements - Alexandr I. Vedenev; Oleg Yu. Kochetov; Andrey A. Lunkov; Andrey S. Shurup; Saltanat S. Kassymbekova (Journal of Marine Science and Engineering, 2023)
The measurements of airborne and underwater noise radiated by a Griffon BHT130 hovercraft were conducted in the Ural-Caspian Channel and in the North Caspian Sea. This type of hovercraft is being used for all-season cargo and crew transportation to oil and gas platforms within the environmentally sensitive area of the Ural River estuary known for its abundant bird and fish fauna. Several field campaigns were organized from 2017 to 2022 to measure and analyze acoustic noise levels simultaneously in the air and underwater at various sites and hovercraft speeds. Airborne noise levels were estimated according to ISO 2922:2020, 2021. Underwater noise study included not only acoustic pressure recordings but also particle velocity measurements with a self-designed pressure gradient sensor (PGS), which is important since the hearing of the majority of fish perceives the sound in terms of particle motion. This study is the first to report the particle velocity levels formed underwater during hovercraft passages. The minimum levels of underwater noise, 100 dB re 1 µPa (pressure), 45 dB re 1 nm/s (particle velocity), and airborne noise, 93 dBA re 20 µPa (pressure), normalized to a distance of 25 m were observed for the hovercraft passages at a cruising speed of 7–15 m/s. Thus, this speed interval can be recommended as an optimum to minimize an acoustic impact on ornitho- and fish fauna. The directivity of the hovercraft noise was estimated for the first time and utilized for noise mapping of the Ural-Caspian Channel. The possible hydrodynamic effect of a passing hovercraft is discussed.